2023
DOI: 10.3389/fneur.2023.1061849
|View full text |Cite
|
Sign up to set email alerts
|

The highest region of muscle spindle abundance should be the optimal target of botulinum toxin A injection to block muscle spasms in rats

Abstract: PurposeThe effective relief of muscle spasticity requires prompt solutions in rehabilitation medicine. This study aimed to reveal that the highest region of muscle spindle abundance is the optimal target of botulinum toxin A (BTX-A) injections for relieve muscle spasm.MethodsSixty adult, male Sprague–Dawley rats with lower limbs spasm caused by stroke after modeling, weighing (200 ± 20) g, were included in this study. The modelrats were divided into four groups: muscle spasm model group (group A), model rats t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The muscle spindles abundances obtained in this experiment were slightly higher than that in the mentioned study, possibly because of the uneven distribution of muscle spindles. This study focused on the INDR, which has a relatively large number of muscle spindles ( Yu et al, 2023 ). Present results indicate that the CRHMSA in the deep cervical muscle aligns with the center of the INDR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The muscle spindles abundances obtained in this experiment were slightly higher than that in the mentioned study, possibly because of the uneven distribution of muscle spindles. This study focused on the INDR, which has a relatively large number of muscle spindles ( Yu et al, 2023 ). Present results indicate that the CRHMSA in the deep cervical muscle aligns with the center of the INDR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the intramuscular nerve dense region (INDR) location is consistent with the motor endplate band and can serve as an alternative target for BTX-A ( Amirali et al, 2007 ; Phadke et al, 2013 ). Other studies have indicated that the muscle spindle, a type of stretch receptor, is not uniformly distributed within the muscle ( Banks, 2006 ), with higher abundance in INDR and motor endplate bands ( Yu et al, 2023 ). After many central nervous system diseases (such as stroke), due to the weakened inhibition of upper motor neurons on the spinal cord, leading to increased excitability of alpha motor neurons, increased sensitivity of Ia type fibers and increased activity of gamma motor fibers in the muscle spindle, the hyperactive stretching reflex can be achieved through the α-γ loop, thereby exacerbating muscle spasms ( Phadke et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, accurate and appropriate BTX-A injection to the target site is essential. Studies have shown that 1 unit of BTX-A can infiltrate muscle tissue 1.5–3 cm 2 , and 2.5–5 units can diffuse into 4.5 cm 2 (Borodic et al 1994 ; Yu et al 2023 ). According to these theories and the results of this experiment, the INDR areas of the piriformis and obturator internus muscles are 5.37 ± 0.32 cm 2 and 13.33 ± 0.61 cm 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle spindles grow at different rates and are highly abundant in the INDR but are not uniformly distributed (Banks, 2006 ). Recent animal studies have demonstrated that the centre of the highest region of muscle spindle abundance (CHRMSA) in the INDR is the optimal target for BTX‐A to block muscle spasticity (Yu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%